Population Structure and Production Performance of Native Chicken as a Source of Local Animal Protein - Estepanus L. S. Tumbal; Tri Jaya Ganeputra; Mery C. Simanjuntak (Jurnal Penelitian Pendidikan IPA, 2025)
Native chickens are an important local source of animal protein in Kalisemen Village, West Nabire District, Nabire Regency, Central Papua. Despite their significant contribution as a local source of animal protein, a thorough understanding of their population structure and production performance remains limited. This research aims to further examine these aspects to optimize the potential of local chickens as a sustainable source of animal protein. This study aims to examine the population structure and production performance of native chickens as a basis for developing sustainable local livestock. Population data were collected based on age and sex categories, while production performance included the number of eggs per parent, chick mortality rate, and number of chickens sold. The results showed a native chicken population of 2,902 with a dominance of adult females (23.36%). Average egg production was 11.02 eggs per parent with a chick mortality rate of 1.96 and an average chicken sale of 6.98 per farmer. This condition shows the potential of native chickens as a local protein source that needs to be supported by better population management and marketing. Recommendations include strengthening female parents, improving chick maintenance, and developing an integrated marketing system. These findings provide important contributions to food security and local livestock development in Central Papua.